PEMBENTUKAN KEPRIBADIAN SISWA MELALUI PROGRAM LITERASI BUDAYA ARAB DI MTS NASYIIN SIDOARJO - Abdul Halim, Habib (MIYAH : Jurnal Studi Islam, 2024)
Abstract: This article aims to discuss the implementation of understanding Arabic cultural literacy in the formation of the personality of grade VIII students at MTs Nasyi'in Sidoarjo. This research uses a qualitative approach with a descriptive method, which involves interviews, observations, and documentary studies. The sample in this study is a grade VII student of MTs Nasyi'in. The results of the study show that factors such as family environment, school, and community play an important role in the formation of students' personalities. Through learning activities involving moral values, students show an attitude of tolerance, manners, and help. Moral education applied in schools not only aims to increase students' knowledge, but also to shape their character to be in accordance with Islamic values. These findings emphasize the importance of collaboration between families, schools, and communities in creating an environment that supports the development of positive personalities in students. It is suggested that the next researcher may be able to develop a moral-based education curriculum sourced from Arab culture with appropriate methods. Keyword: Literacy, Arabic Culture, Student Personality